EFFICIENCY OF MONTELUKAST TREATMENT OF THE CHILDREN, SUFFERING FROM BRONCHIAL ASTHMA - I.I. Balabolkin; I.E. Smirnov; A.V. Liapunov; O.F. Lukina; N.V. Goncharova; V.S. Reutova; A.V. Goriunov ("Paediatrician" Publishers LLC, 2006)
The aim of the present open research was to assess the montelukast efficiency among 41 children, suffering from bronchial asthma. the age of patients was between 6 and 15 years old. Clinical and functional efficiency of montelukast was noted among 85,4% of the patients. montelukast treatment contributed to the decrease of the bronchial asthma recrudescence frequency, reduction of the number of the used betab2bprotoganists, inhaled glucocorticosteroids and increase of tolerance towards the physical load.Key words: bronchial asthma, montelukast, children, treatment.